Evolution of Communication Strategies Used by Universities in Southern Spain on Twitter - Cestino González, Estefanía; Ruiz del Olmo, Francisco Javier (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study examines the evolution of communication strategies on Twitter by 12 universities in southern Spain and Portugal during the pre-lockdown, lockdown, and post-lockdown phases of the COVID-19 pandemic. Based on the analysis of over 7,000 posts, changes were identified in formats, objectives, topics, audiences, and performance. Images were predominant (71.1%), and the use of emojis and hashtags increased. During lockdown, the main objective was to inform, while inspiring and educating gained importance afterwards. The most common topics were events, human and institutional support, and the main audience was the general community. Posts saw the highest engagement during lockdown, reflecting strong social commitment. The study concludes that universities adapted effectively to changing contexts, showing that academic quality does not necessarily ensure greater communicative impact. Emotionally intelligent and context-aware communication management was key, positioning Twitter as an essential institutional tool for maintaining connection during a global crisis.